EDUKASI KESEHATAN REPRODUKSI BAGI REMAJA : MENUJU GENERASI SEHAT DAN AKTIF - Suharni, Suharni; Rosmaini, Rosmaini (Jurnal Abdimas Saintika, 2024)
Adolescence is the age stage where a person begins to act independently without depending on their parents starting at the age of 12 years and above. As the most extensive phase, teenagers experience various simple and complex problems, such as the health of their reproductive organs. The Community Service activities that the researchers participated in were carried out at the Nurul Falah Islamic Boarding School with a focus on providing counseling to 25 teenagers who were active as Islamic boarding school students and female students there. Extension activities will be carried out on Saturday, November 25 2023 from 09.00 am until finished. As a result, this activity went well where the author found two weaknesses, namely the difficulty in carrying out PKM activities and the students being shy.Keyword: Adolescence, Community Service, Nurul Falah, Counseling, Reproductive Health